2014
DOI: 10.1155/2014/183924
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Return in Fear of Spiders: Discrepant Eye Movement and Reaction Time Data

Abstract: Inhibition of return (IOR) refers to a bias against returning the attention to a previously attended location. As a foraging facilitator it is thought to facilitate systematic visual search. With respect to neutral stimuli, this is generally thought to be adaptive, but when threatening stimuli appear in our environment, such a bias may be maladaptive. This experiment investigated the influence of phobia-related stimuli on the IOR effect using a discrimination task. A sample of 50 students (25 high, 25 low in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In particular, a wealth of studies have shown that threatening information attracts attention. Various kinds of threatening stimuli, such as angry faces 3,4 , dangerous animals [5][6][7] , and violent situations 8 , have been included in these studies. Recent evidence has revealed that the automatic processing of threatening information is inherent.…”
Section: The Priority Of Goal-relevant Information and Evolutionarilymentioning
confidence: 99%
“…In particular, a wealth of studies have shown that threatening information attracts attention. Various kinds of threatening stimuli, such as angry faces 3,4 , dangerous animals [5][6][7] , and violent situations 8 , have been included in these studies. Recent evidence has revealed that the automatic processing of threatening information is inherent.…”
Section: The Priority Of Goal-relevant Information and Evolutionarilymentioning
confidence: 99%
“…Indeed, compelling evidence indicates that fear-related animals are preferentially processed ( Macleod and Mathews, 1988 ), which manifests itself in eye-tracking research as longer fixation durations or as greater skin conductance responses compared to neutral stimuli ( Gerdes et al, 2008 , 2009a ; Wiemer et al, 2013 ). Still, the stimuli used in such studies are typically very diverse, e.g., potentially threatening animals like snakes, spiders, insects ( Lipp, 2006 ; Rinck and Becker, 2006 ; Gerdes et al, 2008 , 2009b ; Weymar et al, 2013 ; Berdica et al, 2014 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by a Darwinian perspective of threat assessment, there is a growing literature on human responses to viewing dangerous animals, mostly using photographs of snakes and spiders known to engender phobic responses (see LoBue, Matthews, Harvey, & Stark, 2014). The experimental protocols used in these studies resemble those employed for face perception and typically evaluate subjective attitudes, viewer reaction times, and physiological measures (e.g., Berdica, Gerdes, Pittig, & Alpers, 2014). Controlled presentations of animal images in laboratory settings can provide information on the specific perceptual properties of these animals that attract attention and influence rapid decision making, including aesthetic preferences (cf.…”
Section: Experimental Studies Of Human Responses To Lion Imagesmentioning
confidence: 99%